Pengaruh Hedonic Shopping Motivation, Shopping Lifestyle, dan Fashion Involvement terhadap Impulse Buying pada Program Flash Sale di Aplikasi Shopee (Studi Empiris pada Mahasiswa Fakultas Ilmu Pendidikan UMMAH) - Mita, Cut; Ningsih, Sulistio; Yanti, Syafridha (Fakultas Ekonomi, 2025)
This study aims to analyze the influence of Hedonic Shopping Motivation, Shopping Lifestyle, and Fashion Involvement on Impulse Buying during flash sale programs on the Shopee application. The research adopts a quantitative approach with a causal associative research design. The respondents consisted of students from the Faculty of Education at Universitas Muhammadiyah Mahakarya Aceh. The results reveal that, partially, neither Hedonic Shopping Motivation nor Shopping Lifestyle have a significant effect on Impulse Buying. However, Fashion Involvement shows a significant influence on Impulse Buying behavior. Simultaneously, the results of the F-test demonstrate that Hedonic Shopping Motivation, Shopping Lifestyle, and Fashion Involvement collectively have a significant effect on Impulse Buying during Shopee's flash sale program among students of the Faculty of Education at UMMAH. The model explains 51.6% of the variance in impulse buying behavior, while the remaining 48.4% is influenced by other factors not examined in this study.